IMPLEMENTASI STRATEGI PEMBELAJARAN METAKOGNITIF UNTUK MENINGKATKAN KEMAMPUAN METAKOGNITIF DAN PRESTASI BELAJARA FISIKA SISWA SMA - Umam, Hilman Imadul (2013)
Research has been conducted to determine the application of metacognitive learning strategies in improving metacognitive skills and achievement of high school students learn physics. This research is motivated by the lack of awareness and control of students' skills in cognitive ability of students to learn so that awareness is very low and lead to academic achievement especially in physics lessons to be less than the maximum. The learning process has not been able to provide the opportunity for students to know how he should learn, know the capabilities and modalities that are owned, and know the best strategies for effective learning, causing students to learn self-reliance is very low. Independent learning is an asset for students to continue their long journey to meet the intellectual needs of the students so it is very important. Independence can be built when students have the awareness to manage and regulate their cognitive ability to respond to a situation or problem. Awareness can be purchased by students when he has a metacognitive abilities. This study aims to see an increase in metacognitive ability and achievement of high school students studying physics after the implementation of metacognitive learning strategies. Metacognitive abilities measured in this study related to the knowledge and metacognitive skills. Metacognitive knowledge includes declarative knowledge, procedural, and conditional. Whereas metacognitive skills include skills for identifying, planning, meonitoring action, and evaluation. The method used in this study was pre-experimental research design with One-Group Pretest-Posttest Design. The instrument used for data retrieval is learning achievement test, test metacognitive knowledge, learning journals, and learning feasibility observation sheet. The results showed an increase in academic achievement and metacognitive knowledge seen from the N-gain. As for the metacognitive skills saw an increase of the percentage of students who undertake every stage of metacognitive skills. Increased metacognitive ability and achievement was due to metacognitive learning strategies can be implemented with very good category based on the results of observations. In other words, metacognitive learning strategies to improve high school students' metacognitive abilities. Keyword : Metacognitive learning strategies, metacognitive abilitiy Telah dilakukan penelitian untuk mengetahui penerapan strategi pembelajaran metakognitif dalam meningkatkan kemampuan metakognitif dan prestasi belajar fisika siswa SMA. Penelitian ini dilatarbelakangi oleh rendahnya kesadaran dan kemampuan siswa dalam mengontrol kemampuan kognitifnya sehingga kesadaran siswa untuk belajar sangat rendah dan menyebabkan prestasi belajar khususnya pada pelajaran fisika menjadi kurang maksimal. Proses pembelajaran belum bisa memberikan kesempatan kepada siswa untuk mengetahui bagaimana seharusnya ia belajar, mengetahui kemampuan dan modalitas yang dimiliki, dan mengetahui strategi terbaik untuk belajar efektif sehingga menyebabkan kemandirian siswa untuk belajar sangat rendah. Kemandirian belajar merupakan sebuah modal bagi siswa untuk meneruskan perjalanan panjang mereka dalam memenuhi kebutuhan intelektualitasnya sehingga sangat penting dimiliki siswa. Kemandirian tersebut dapat dibangun ketika siswa memiliki kesadaran dalam mengelola dan mengatur kemampuan kognitifnya dalam merespon situasi atau persoalan. Kesadaran tersebut dapat dimiliki oleh siswa ketika ia memiliki kemampuan metakognitif. Penelitian ini bertujuan untuk melihat peningkatan kemampuan metakognitif dan prestasi belajar fisika siswa SMA setelah diterapkannya strategi pembelajaran metakognitif. Kemampuan metakognitif yang diukur dalam penelitian ini terkait pada pengetahuan dan keterampilan metakognitif. Pengetahuan metakognitif meliputi pengetahuan deklaratif, prosedural, dan kondisional. Sedangkan untuk keterampilan metakognitif meliputi keterampilan mengidentifikasi, merencanakan, meonitoring tindakan, dan evaluasi. Metode penelitian yang digunakan pada penelitian ini adalah pre-eksperimental dengan desain penelitian One-Group Pretest-Posttest Design. Instrumen yang digunakan untuk pengambilan data adalah tes prestasi belajar, tes pengetahuan metakognitif, jurnal belajar, dan lembar observasi keterlaksanaan pembelajaran. Hasil penelitian menunjukan adanya peningkatan prestasi belajar dan pengetahuan metakognitif dilihat dari nilai N-gain. Sedangkan untuk keterampilan metakognitif terlihat adanya peningkatan dari persentase jumlah siswa yang melakukan tiap tahapan keterampilan metakognitif. Peningkatan kemampuan metakognitif dan prestasi belajar tersebut terjadi karena strategi pembelajaran metakognitif dapat diimplementasikan dengan kategori sangat baik berdasarkan hasil observasi. Dengan kata lain strategi pembelajaran metakognitif mampu meningkatkan kemampuan metakognitif siswa SMA. Kata kunci: Strategi pembelajaran metakognitif, Kemampuan metakognitif,